2018
DOI: 10.1098/rsos.180841
|View full text |Cite
|
Sign up to set email alerts
|

Two sources of bias explain errors in facial age estimation

Abstract: Accurate age estimates underpin our everyday social interactions, the provision of age-restricted services and police investigations. Previous work suggests that these judgements are error-prone, but the processes giving rise to these errors are not understood. Here, we present the first systematic test of bias in age estimation using a large database of standardized passport images of heterogeneous ages (n = 3948). In three experiments, we tested a range of perceiver age groups (n = 84), and found average age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 32 publications
2
39
0
Order By: Relevance
“…From the Guess data we delete all guesses that are more than two times the standard deviation away from the mean age guess on a photograph. We further remove all guesses on photographs that have less than 10 guesses, since it is known that substantial uncertainty in rating ages exists 19,22,23 . This uncertainty mainly arises within guessers among repeated guesses and to a much lower degree among guessers 24 .…”
Section: Data Recordsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the Guess data we delete all guesses that are more than two times the standard deviation away from the mean age guess on a photograph. We further remove all guesses on photographs that have less than 10 guesses, since it is known that substantial uncertainty in rating ages exists 19,22,23 . This uncertainty mainly arises within guessers among repeated guesses and to a much lower degree among guessers 24 .…”
Section: Data Recordsmentioning
confidence: 99%
“…When they rated ages on AgeGuess.org, they were disappointed to not have performed any different than the users on AgeGuess.org (data not published). Also, when comparing the variance (standard deviation, SD) in the difference between chronological age and perceived age between highly controlled studies 19,22–24 and the AgeGuess data the variance in the difference was comparative to the data generated by the citizen scientists (6–8 in classical studies, 6.9 for the AgeGuess data). This similarity in age estimation might not be expected since the images in the controlled studies have been obtained under strict standardized settings, such as controlled posture, lighting, face expression, clothing, background, distance to camera, make-up, and without accessories such as hats, jewellery, or glasses 8 .…”
Section: Data Recordsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Studies have shown that facial aging is the most important factor in perceived age, which accounts for up to 20% of the variance in the social evaluation of faces. 10,11 It has been suggested that a significant proportion of facial cosmetic surgery patients seek antiaging procedures due to negative societal views about aging. 12 According to the American Society of Plastic Surgeons, >400,000 facelift, forehead lift, neck lift, and blepharoplasty surgeries were performed in 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Although we prevented any systematic biases of block order by counterbalancing blocks, slightly different results might have been obtained with randomized presentation. This is because age ratings for both faces(Clifford, Watson, & White, 2018;Schweinberger et al, 2010) and voices(Zäske & Schweinberger, 2011) show sequential dependencies, in the form of contrastive adaptation. Note also that blocking stimuli by age (as compared to randomized presentation) would be expected to promote contrastive adaptation, and thus might have counteracted (rather than produced) the abovementioned biases of overestimating young speakers' ages and underestimating old speakers' ages.…”
mentioning
confidence: 99%